Crack in the Rearview Mirror: Deconstructing Drug war Mythology - Reinarman, Craig (Social justice, 2004)
Part of a special issue on resisting militarism and globalized punishment. The crack scare that occurred in the U.S. in the 1980s, which resulted in Congress passing new laws that extended criminal sentence lengths for crack offenses, is discussed. Five of the myths about crack that contributed to the passing of these laws are deconstructed. These myths are: crack is not the same drug as cocaine; crack is inevitably and instantly addictive; crack is widely used in all sectors of society; crack use leads to crime and violence; and crack use during pregnancy results in crack babies.